On the stability and periodicity for some differential equations with delay - Touahri, khaoula; Guettar, chaima (university of eloued جامعة الوادي, 2023)
هٌعب الاستقشاس دوسا يه اً ف الا ظَ تً انذ اٌُي كٍ تٍ وانتحكى زًٌٍ خاص تٍ ان سًاساث غ شٍ ان ضًطشبت بح ثٍ أ الإضطشاباث انصغ شٍة تسبب فقط تغ شٍاث صغ شٍة ف سهىك ان ظُاو.ف هز ان زًكشة سَتخذو تق اٍُث ان قُطت انثابتت نهحصىل عهى تَائج الاستقشاس نه عًادنت انتفاضه تٍStability plays an important role in dynamic sestems and contol characterizes the characteristic of non turbulent paths so that small perturbations cause only small changes in the behavior of the systeme .In this memiory we use fixed point techniques to obtain the stability results of the integral differential equation with functional delays with the introduction of some hypotheses in order to find a periodic solution positive for the delay differential equation. With exemples to be given for clarification. انتكايه تٍ يع انتأخ شٍ انىظ فٍ يع تقذ ىٌ بعض انفشض اٍث ي اجم ا جٌاد حم دوسي يىجب
mémoire master matimatuque
Keywords: نه عًادنت انتفاضه تٍ راث انتأخ شٍ.يع اعطاء ايثهت نهتىض حٍ.